 Questions & Answers    Question Answers

# The sum of all real values of x satisfying the equation ${\left( {{x^2} - 5x + 5} \right)^{{x^2} + 4x - 60}} = 1$ is  Answer Verified

Given, $(x^{2} - 5x + 5)^{x^{2} + 4x - 60} = 1$

Clearly, this is possible when

I. $x^{2} + 4x - 60 = 0$ and $x^{2} - 5x + 5 \neq 0$

or

II. $x^{2} - 5x + 5 = 1$

III. $x^{2} - 5x + 5 = - 1$ and $x^{2} + 4x - 60$ = Even integer.

Case I  When $x^{2} + 4x - 60 = 0$

⇒                    $x^{2} + 10x - 6x - 60 = 0$

⇒                   $x(x + 10) - 6(x + 10) = 0$

⇒                   (x + 10)(x - 6) = 0

⇒                   x = -10 or x = 6

Note that, for these two values of $x, x^{2} - 5x + 5 \neq 0$

Case II  When  $x^{2} - 5x + 5 = 1$

⇒                      $x^{2} - 5x + 4 = 0$

⇒                      $x^{2} - 4x - x + 4 = 0$

⇒                      x(x - 4) -1(x - 4) = 0

⇒                      (x - 4)(x - 1) = 0 ⇒ x = 4 or x = 1

Case III  When   $x^{2} - 5x + 5 = -1$

⇒                        $x^{2} - 5x + 6 = 0$

⇒                        $x^{2} - 2x - 3x + 6 = 0$

⇒                        x(x - 2) - 3(x - 2) = 0

⇒                        (x - 2)(x - 3) = 0

⇒                        x = 2 or x = 3.

Now, when x = 2, $x^{2} + 4x - 60 = 4 + 8 - 60 = - 48$, which is an even integer.

When x = 3, $x^{2} + 4x - 60 = 9 + 12 - 60 = -39$, which is not an even integer.

Hence the sum of all real values of x = -10 + 6 + 4 + 1 + 2 = 3.

Bookmark added to your notes.
View Notes
The Language of Mathematics  Different Forms of the Equation of Line  Sum of Squares  Intercept Form of the Equation of a Plane  Solve the Pair of Linear Equation  What is the Formula of Tan3A?  What is the Scattering of Light?  The Voice of the Rain Summary  Sum of Squares Formula  Sum of Odd Numbers  